Definitions (and Current Controversies) of Diabetes and Prediabetes - Buysschaert, Martin; Medina, Jose-Luis; Buysschaert, Benoit; Bergman, Michael (Current Diabetes Reviews, 2016)
Diagnosis of type 2 diabetes and prediabetes is mandatory. Chronic hyperglycemia in diabetes is associated with long-term micro- and macrovascular as well as with neurological complications. Prediabetes predisposes patients to develop diabetes and macrovascular disease. Diagnosis of diabetes is established on (at least) one of the following criteria: a fasting plasma glucose ≥ 126 mg/dl (7.0 mmol/l), a casual plasma glucose ≥ 200 mg/dl (11.1 mmol/l) in the presence of symptoms, a 2-h plasma glucose during the 75-g oral glucose tolerance test (OGTT) ≥ 200 mg/dl (11.1 mmol/l) and/or an HbA1c ≥ 6.5%. Prediabetes is defined by the Position Statement of the American Diabetes Association as a fasting plasma glucose between 100 and 125 mg/dl (5.6 - 6.9 mmol/l) [a condition called Impaired Fasting Glucose] and/or by a 2-h plasma glucose during OGTT 140 - 199 mg/dl (7.8 - 11.0 mmol) [Impaired Glucose Tolerance] and/or a HbA1c level 5.7 - 6.4%, with however some potential discordance between tests. The threshold of fasting plasma glucose defining Impaired Fasting Glucose as well as the adequacy of HbA1c as a correct diagnostic tool for prediabetes is still debated.
Keywords: Complications